Evaluation of energy absorption of aluminium tube partially wrapped with glass/epoxy using Taguchi Method - ABBAS, TAHIR (2017)
Various kinds of thin-walled tubes made from different materials have been studied by many researchers for energy absorbers in vehicle structures. Most of the studies were based on metallic or fiber reinforced polymer (FRP) tubes. Only a few studies were carried out on hybrid tubes. A hybrid tube has more energy absorption capability as compared to metal or composite tube. However, the specific energy absorption capability of the hybrid tube to achieve good efficiency has not been investigated in detail. The aim of this study was to focus on the partial wrapping of the light-weight thin-walled aluminium tube with glass/epoxy, which is very significant to enhance the safety of automobiles. Partially wrapped aluminium tube samples have been prepared according to the L9 Taguchi design orthogonal array, by applying various fiber orientations, composite layers and partially wrapped area via filament winding process. Failure modes and specific energy absorption and crush force efficiency of partially wrapped aluminium tube samples have been studied under quasi-static loading. The study revealed that the optimum combination of fiber orientation, composite layers, and the partially wrapped area was ±55◦, 6, and 30% respectively. This combination was achieved via the analysis of variance (ANOVA), and the main plot effect analysis. Moreover, this combination also has 81.92%, and 62.08% higher values of specific energy absorption (SEA), and 47.67% and 1.54% more values of crush force efficiency (CFE) as compared to the simple aluminium tube and its predecessor the steel tube, respectively. The results show the two-lobe diamond failure mode of this combination (±55◦, 6, and 30%). The findings demonstrate the ability of the approach as a reliable and light-weight solution for energy absorbers with a high value of SEA and CFE.